Penguatan Pendidikan Karakter Dalam Pembelajaran Sosiologi - Mitrasiabila Oe (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This study aimed to know (1) character education in sociology learning for students and (2) the obstacles students face in building character in the learning process at SMA PGRI Kupang. The research method used in this study was qualitative. The subjects of this study consisted of school principals, sociology teachers, and students. Data collection techniques include observation, interviews, documentation, and data analysis techniques through data reduction, data presentation, and conclusion. The research results show several findings; firstly, character education is the. Religious people pray together before doing the activity and after the activity. Spirit of nationalism, namely carrying out flag ceremonies every Monday and activities related to nationalism. The spirit of gotong royong is to carry out activities to clean up the school environment. Second is a sense of integrity; students are taught to be responsible for the tasks given, such as doing assignments. The two obstacles in the formation of character education at SMA PGRI Kupang, namely the family environment, which can influence the strengthening of students' character education, are hampered, and the lack of discipline of students do not follow the rules that exist in schools which affect the learning process of students who are hampered.